Contraceptive Use Disparities in Asian American Women in 2015–2016: California Health and Interview Survey - Hui Xie; Yannan Li; Chi Wen; Qian Wang (Sexes)
Background: Consistent use of effective contraceptives is directly associated with a lower risk of unintended pregnancies, a significant public health burden in the U.S. The Asian American population is heterogeneous and fast-growing. However, patterns and disparities in contraceptive use among Asian American women, particularly within racial/ethnic subgroups, have been understudied, hindering effective family planning. Objectives: This study aimed to identify the prevalence of contraceptive use and its pattern in Asian American women using the 2015–2016 California Health and Interview Survey (CHIS) data, with a focus on different Asian ethnic subgroups. Study Design: A composite score of acculturation level (0–5) was created based on place of birth, years in the U.S., and language spoken at home. Data on demographics, self-rated health, contraceptive use, and related information were collected from women aged 18–44 years who were at risk of unintended pregnancy. Adjusted multivariable logistic regressions were conducted to examine contraceptive use and patterns in relation to race/ethnicity and other factors. Results: Over 18.20% of the overall sample (pop estimated N = 16,177,759) were Asian Americans, and among them, 24.62% were Chinese, followed by other Asian subgroups (28.83%), Filipina (25.49%), Korean (11.25%), and Vietnamese (9.80%). Overall, Filipina, Korean, and Vietnamese women were less likely to use contraception compared to their non-Hispanic White (NHW) peers, whereas acculturation level was positively associated with contraceptive use. Among different types of contraceptives, Filipina, Korean, and Vietnamese women were less likely to use long-acting reversible contraceptives compared to NHW. Such racial/ethnic disparities were not observed with less or moderately effective contraceptives. Conclusions: Patterns of contraceptive use and associated disparities varied among Asian American subgroups. Providers working with Asian American women should be aware of these racial disparities in contraceptive use and seek ways to address barriers to effective contraception use in this diverse population in order to provide culturally competent family planning services.